Phenotyping the autonomic nervous system in pregnancy using remote sensors: potential for complication prediction - Sharifi-Heris, Zahra; Yang, Zhongqi; Rahmani, Amir M.; Fortier, Michelle A.; Sharifiheris, Hamid; Bender, Miriam (Frontiers in Physiology, 2023)
Objectives: Autonomic Nervous System (ANS) plays a central role in dynamic adaptation during pregnancy in accordance with the pregnancy demands which otherwise can lead to various pregnancy complications. Despite the importance of understanding the ANS function during pregnancy, literature lacks sufficiency in the ANS assessment. In this study we aimed to identify HRV function during second and third trimesters of pregnancy and 1 week after childbirth, and its relevant predictor(s) in healthy pregnant Latina individuals in Orange County, CA.Materia and method: N=16 participants were enrolled into the study from which N=14 (N=13 healthy and n=1 complicated) participants proceeded to analysis phase. For the analysis, we conducted supervised machine learning modeling including Hierarchical Linear Model (HLM) to understand the association between time and HRV, and Random Forest Regression (RFR) to investigate the factors may affect HRV during preganncy. T-test was used for exploratory analysis to compare the complicated case with healthy pregnancies.The results of HLM analysis showed a significant positive relationship between time (day) and average HRV (estimated effect= 0.06; p<0.0001), regardless of being healthy or complicated, indicating that HRV increases during pregnancy significantly. RFR results identified some lifestyle and sociodemographic factors such as activity, sleep, diet, and mental stress as important predictors for HRV changes in addition to time. The findings of T-test indicated that the average weekly HRV of healthy and non-healthy subjects differed significantly (p<0.05) during 17 weeks of the study.It is important to focus our attention on potential autonomic changes, particularly the possibility of increased parasympathetic activity as pregnancy advances. This observation may challenge existing literature that often suggests a decline in parasympathetic activity toward the end of pregnancy. Moreover, our findings indicated the complexity of HRV prediction, involving various factors beyond the mere passage of time. To gain a more comprehensive understanding of this dynamic state, future investigations should delve into the intricate relationship between autonomic activity, considering diverse parasympathetic and sympathetic metrics, and the progression of pregnancy.